Load-carrying capacity of reinforced concrete plates аccording to different yield criteria - Ordon-Beska, Beata (Видавництво Львівської політехніки, 2013)
This paper is devoted to the comparision of four yield criteria used for reinforced concrete plates with the amount of reinforcement not exceeding the balanced reinforcement. The basis of the assessment was the conformity of theoretical results with experimental results of tests on some series of slabs subjected to a homogeneous moment field load. Порівняно чотири критерії локального пошкодження залізобетонних плит з рівнем армування менше граничного. Основою оцінки була точність збігу результатів теоретичних розрахунків з результатами лабораторних досліджень чотирьох серій плит, завантажених однорідним полем моментів.
Keywords: reinforced concrete plates; yield criterion; laboratory tests; statistics analysis; критерій пластичності; залізобетонні плити; лабораторні дослідження; статистичний аналіз